Standard Vs Mini-Percutaneous Nephrolithotomy for Staghorn Stones - Naveed Sultan, Nisar Ahmad Khan, Abdul Aziz, Mian Shabbir Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Objective of this study was to compare the effectiveness of standard and mini-percutaneous nephrolithotomy in treating staghorn stones Methodology: From July 2017 to June 2019, In Institute Of Kidney Diseases (PGMI) Hayatabad Medical Complex Peshawar a tertiary care hospital we conducted a randomized controlled trial to determine the stone-free rate for patients with staghorn stones (Total duration of the study was 2 years). The trial included 150 patients separated into two groups: one that received standard- and mini-PCNL surgeries. Each patient was randomly assigned to undergo one of the two procedures, with 50% receiving standard PCNL and the other 50% mini-PCNL. Durations of surgical procedures, length of hospital stay, complications, and pain levels were all measured during the study. Result: 150 patients with a mean age of 51.2 years (range, 18-85 years) were included in this research. 88% of the participants were men and 16% were women. Success rates for standard PCNL and mini-PCNL were 97.3% and 90.7%, respectively (p=0.04). Additionally, compared to the standard-PCNL group (105.3 minutes and 3.3 days, respectively), the mini-PCNL group had a considerably reduced mean operation time (80.2 minutes) and a shorter mean hospital stay (2.2 days) (p 0.001). Standard PCNL also had a higher overall complication rate than mini-PCNL (26% vs. 13%, p = 0.038). In addition, the mini-PCNL group had considerably less postoperative discomfort (p 0.001). Conclusion: When controlling staghorn stones, Mini-PCNL has shown to be a reliable and safe solution that offers a number of benefits over conventional Standard-PCNL. Mini-PCNL clearly outperforms standard PCNL in terms of lowering postoperative pain, hospital stays, and operating room time. As a result, Mini-PCNL is gradually becoming into the preferred operational strategy for effectively controlling staghorn stones. Keywords: Percutaneous nephrolithotomy, staghorn stones, stone-free rate, surgical time, hospital stay, complications, postoperative discomfort.